Toxicity of Natural Insecticides on Leptocorixa acuta - Elisabeth Nanik Kristalisasi; Badiatud Durroh; Endah Puspitojati; Bayu Adirianto; Agus Manto (Tropical Plantation Journal, 2022)
The basic concept of organic farming prevents synthetic chemical compounds from using fertilizers, pesticides, and growth regulators. Natural insecticides are alternative pesticides in pest control on plants because they are available around us and have a good impact on the sustainability of the agricultural environment. This study aims to examine the level of toxicity of several alternative insecticides in controlling the walang sangit  (Leptocorixa acuta). The research in the laboratory and greenhouse of Instiper Yogyakarta uses 3 natural ingredients, namely neem leaves, tobacco leaves, and C. Odorata weed leaves at 2 stages of L. acuta on instra 3-4 and adults. Observations were made by looking at pest mortality, attack rate, and yield and analyzed using SPSS 16 software. The results showed that tobacco leaf extract was the most effective source of insecticide, with a mortality rate of up to 90% and damage rates below 9%.